Appendicular Perforation in Pregnancy - Neupane, Rashik; Shrestha, Buddhi Kumar; Baniya Chhetri, Puja; Baral, Kamal Raj; Joshi, Jyotsna; Belbase, Narayan Prasad (Journal of College of Medical Sciences-Nepal, 2024)
In this case study, a third-trimester primigravida faced the rare challenge of a perforated appendix followed by successful perinatal outcome. Despite inconclusive imaging results from ultrasound and MRI, clinical progression guided the diagnosis. Timely intervention via emergency laparotomy, involving obstetric and gastro-surgical teams, averted further complications, ensuring a favorable outcome for both mother and baby. The complexities of diagnosing appendicitis during pregnancy, particularly when perforated, were emphasized. This instance underscored the pivotal role of a multidisciplinary approach, meticulous surgical planning, and attentive postoperative care, showcasing how prompt intervention and holistic management are paramount in navigating such intricate scenarios during pregnancy.